Hierarchy of Needs and Motivation of New Students' Study at University - A 'Ainun Zeva Zachary; Murdianto Murdianto (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme)
The motivation to fulfill needs is a primary factor driving every action, including pursuing higher education. This study employed a quantitative-descriptive approach using a survey to map the hierarchy of needs and motivations of students studying at Universitas Negeri Yogyakarta (UNY). The research aimed to identify the primary needs and types of motivation among first-semester students of the Sociology Education Program at UNY for the 2023/2024 academic year. The population consisted of 100 new students, with a sample of 34 students (34%) selected randomly. Data were collected through an online questionnaire and analyzed descriptively using percentages. The findings revealed that most first-semester students were driven by the need for self-actualization (70.6%), while 29.4% were motivated by the need for esteem. Furthermore, intrinsic motivation dominated (82.4%) compared to extrinsic motivation (17.6%). This study concludes that self-actualization needs and intrinsic motivation are the primary factors encouraging new students to study at Universitas Negeri Yogyakarta.